Gambaran logam berat merkuri (Hg) pada kuku penambang emas di Nagari Koto Tuo, Sijunjung Sumatera Barat - Dewi Yudiana Shinta; Herix Sonata MS; Mulyadi Mulyadi; Merry Thressia; Yolanda Oktarina (Jurnal Zona, 2022)
Unlicensed Gold Mining (PETI), was found in 4 districts in West Sumatra including, Dharmasraya covering an area of 1,773 ha, Solok 1,533 ha, Solok Selatan 2,559 ha, and Sijunjung 1,103 ha. PETI is a traditional gold mining activity, the results are processed using the amalgamation method. The amalgamation process in the PETI activity will result in environmental degradation caused by the washing process carried out in the river and the process of refining gold ore by burning which produces mercury vapor (Hg) which evaporates in the air. The amalgamation process can cause negative impacts in the form of environmental pollution by mercury vapor as a result of the process. As much as 10 - 30% of the mercury used in the gold amalgamation process will be released into the environment. The main health problems caused by mercury vapor occur in the brain, lungs, central nervous system and kidneys. The purpose of this study was to describe the level of toxicity that occurs in humans through nails on illegal gold miners in Nagari Koto Tuo Sijunjung, West Sumatra. The benefit of the research is as information that is conveyed to local governments and people who are exposed to heavy metals for the dangers they face. The research method is an observational study with a cross sectional study design, which is a study in which the variables including risk factors and variables including effects are observed simultaneously at the same time. The number of samples used in this study were 13 people. Samples were taken using accidental sampling technique. The method used to determine levels of metallic mercury in nails is wet destruction and examined by AAS. The results of this study used 13 active gold miners with a working period of 20.10 and 5 years with mercury levels of 10.31 mg/kg, 10.04 mg/kg, and 7.30 mg/kg. Based on the results of the standard deviation (SD) test, it was found that the average level of mercury in the nails of gold miner Koto Tuo, Sijunjung was 9.21 mg/kg with an average working life of 34 years and a standard deviation of 1.665. Mercury is a neurotoxin if used in high doses can damage the person's organs.